2012
DOI: 10.1017/s1355617712000227
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Predictors of Cognitive Functioning in Older Adults

Abstract: Background Few studies have applied multiple imaging modalities to examine cognitive correlates of white matter. We examined the utility of T2-weighted MRI-derived white matter hyperintensities (WMH) and diffusion tensor imaging-derived fractional anisotropy (FA) to predict cognitive functioning among older adults. Methods Quantitative MRI and neuropsychological evaluations were performed in 112 older participants from an ongoing study of the genetics of Alzheimer’s disease (AD) in African Americans. Regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 88 publications
7
34
1
Order By: Relevance
“…Conversely, another theory follows the retrogenesis model and proposes that white matter change is independent of the gray matter pathology. The white matter will follow the reverse order of myelinogenesis, in which white matter will degenerate first in the late-myelinating WM tracts, such as the inferior and super longitudinal fasciculus and the uncinate fasciculus (Meier et al, 2012). In short, our current results suggest that WML detected in T2 or FLARE images of MCI cannot differentiate different subtypes of MCI and is yet to be a reliable prognostic marker in determining the risk of dementia.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Conversely, another theory follows the retrogenesis model and proposes that white matter change is independent of the gray matter pathology. The white matter will follow the reverse order of myelinogenesis, in which white matter will degenerate first in the late-myelinating WM tracts, such as the inferior and super longitudinal fasciculus and the uncinate fasciculus (Meier et al, 2012). In short, our current results suggest that WML detected in T2 or FLARE images of MCI cannot differentiate different subtypes of MCI and is yet to be a reliable prognostic marker in determining the risk of dementia.…”
Section: Discussionmentioning
confidence: 63%
“…First, WML is associated with reduced cognitive functioning in MCI. It is widely accepted that a severe grade of WML has a detrimental impact on cognitive functioning including executive function, attention, processing speed, and global cognition (Jokinen, Lipsanen, & Schmidt, 2012;Meier et al, 2012;Pantoni, Poggesi, & Inzitari, 2007;Prins & Scheltens, 2015;Xiong & Mok, 2011). Second, the location or the spatial distribution of the WML has a differential impact on cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…White matter abnormalities and changes in myelin genes have been linked to multiple psychiatric disorders (including schizophrenia and obsessive-compulsive behavior (9, 36)), as well as in Alzheimer disease (37). Meanwhile, recently identified models of compulsive grooming and trichotillomania similar to that displayed by our conditional knock-out mice involve genes important for neural (i.e.…”
Section: Discussionmentioning
confidence: 84%
“…Fractional anisotropy (FA) is a commonly reported scalar metric derived from the diffusion tensor that provides a measure of the directionality of water diffusion. Research has shown that while FA and WMH are related, they likely reflect distinct structural manifestations of white matter (Vernooij et al 2009; Meier et al 2012; Maillard et al 2013; Aine et al 2014), and thus may both be valuable for assessing the extent of white matter disturbances associated with HIV.…”
Section: Introductionmentioning
confidence: 99%